Family Environment in Children With Hearing Aids and Cochlear Implants: Associations With Spoken Language, Psychosocial Functioning, and Cognitive Development. Issue 4 (July 2020) - Holt, Rachael Frush; Beer, Jessica; Kronenberger, William G.; Pisoni, David B.; Lalonde, Kaylah; Mulinaro, Lindsay
Abstract : Objectives: To examine differences in family environment and associations between family environment and key speech, language, and cognitive outcomes in samples of children with normal hearing and deaf and hard-of-hearing (DHH) children who use hearing aids and cochlear implants. Design: Thirty families of children with normal hearing (n = 10), hearing aids (n = 10), or cochlear implants (n = 10) completed questionnaires evaluating executive function, social skills, and problem behaviors. Children's language and receptive vocabulary were evaluated using standardized measures in the children's homes. In addition, families were administered a standardized in-home questionnaire and observational assessment regarding the home environment. Results: Family environment overall was similar across hearing level and sensory aid, although some differences were found on parental responsivity and physical environment. The level of supportiveness and enrichment within family relationships accounted for much of the relations between family environment and the psychosocial and neurocognitive development of DHH children. In contrast, the availability of objects and experiences to stimulate learning in the home was related to the development of spoken language. Conclusions: Whereas broad characteristics of the family environments of DHH children may not differ from those of hearing children, variability in family functioning is related to DHH children's at-risk speech, language, and cognitive outcomes. Results support the importance of further research to clarify and explain these relations, which might suggest novel methods and targets of family-based interventions to improve developmental outcomes.